Role of Pro-inflammatory and Immunoregulatory Cytokines in Pathogenesis of Chronic Gastritis - Al-Lami, Narjis A.R.; Al-joofy, Ikbal K. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Chronic gastritis (CG) is histopathological entity characterized by chronic inflammation of the stomach that mostly caused by Helicobacter pylori, development of inflammation in gastric mucosa result in release of pro- and anti- inflammatory cytokines .This study aimed to shed light on the role of cytokines (IFN-γ, IL-8, IL-4, IL-10, and GM-CSF) in the development and prognosis of CG among Iraqi patients. Patients and methods: 100 Iraqi patients with CG (61 male and 39 female) with age range (10-79) year, were involved in this stady while attending Specialist Hospital of Disease of Liver and Gastrointestinal System at Baghdad Medical City from Nov. 2007 to Apr. 2008. Patients divided according to histological diagnosis into three groups : 66 with active CG, 21 with Superficial CG and 13 with Inactive CG . All Patients were investigated for infection with H. pylori by histological and for quantitative estimation of serum anti H. pylori (IgG) by Enzyme Linked Immunosorbent Assay (ELISA), and Amplified Sensitivity Immuno Assay (EASIA) technique to measure the level of cytokines (IFN-γ, IL-8, IL-4, IL-10, and GM-CSF) for both patients and healthy control groups. Results: Incidence of H. pylori is (66٪) among all patients, highly significant increased (p<0.01) in serum level of anti H. pylori in patient groups: Active CG, Superficial CG and Inactive CG respectively and significant increased (p<0.01) trend of IFN-γ, IL-8, IL-4, IL-10, and GM-CSF in all patient groups as compared with healthy control. Conclusions: High frequency of H. pylori in patient reflect the important role of H. pylori in etiopathogenesis of CG. Increased serum level of cytokines (IFN-γ, IL-8, IL-4, IL-10, and GM-CSF) propaply play crucial role in driving inflammatory process and promoting gastric mucosa destruction in CG, regulation of these cytokines is consider as an important therapeutic goal.